Weak Makes It Powerful: The Role of Cognate Small Molecules as an Alloy Donor in 2D/1A Ternary Fullerene Solar Cells for Finely Tuned Hierarchical Morphology in Thick Active Layers. Issue 3 (21st January 2020) - Fan, Qunping; Liu, Tao; Zhang, Ming; Su, Wenyan; Méndez‐Romero, Ulises A.; Yang, Tao; Geng, Xinjian; Hou, Lintao; Yu, Donghong; Liu, Feng; Yan, He; Wang, Ergang
Abstract: Herein, a novel small molecule donor is first developed, FSM6, which is a cognate molecule to BTR possessing similar molecular structure with comparable optical absorption but different crystallinity. The efficient fullerene‐type ternary small molecular solar cells (SMSCs) based on an alloy donor of BTR and FSM6 in a thick film of 250 nm reveal the improved hierarchical phase separation morphology and molecular structural order of ternary active layers with improved crystallinity of the key donor component BTR. Furthermore, FSM6 as the key third component also plays a role of charge transfer accelerator in ternary SMSCs. As a result, the optimal ternary SMSCs based on BTR:FSM6:PC71 BM achieve a high power conversion efficiency (PCE) up to 10.21% with the synergistically improved open‐circuit voltage of 0.950 V, short‐circuit current density of 13.85 mA cm −2, and fill factor of 77.6%, in comparison with either the binary SMSCs of BTR:PC71 BM (PCE = 9.37%) or FSM6:PC71 BM (PCE = 8.00%). This work provides a promising methodology to optimize device morphology for high‐performance ternary SMSCs by combining two cognate small molecules with similar absorption spectra but different crystallinity as an alloy donor. Abstract : An efficient small molecules:fullerene ternary solar cell based on two small molecule donors, BTR and newly synthesized FSM6, with similar molecular structures and absorption spectra but different crystallinity is fabricated. Due to the FSM6‐induced morphology optimization, the ternary devices with a thick active layer achieve a high power conversion efficiency (PCE) of 10.21%.